Mass selection for survival and resistance to OsHV-1 infection in Crassostrea gigas spat in field conditions: response to selection after four generations - Degremont, Lionel; Nourry, Max; Maurouard, Elise (Aquaculture, 2015)
The ostreid herpesvirus 1 (OsHV-1) is one of the major pathogens affecting the Pacific oyster Crassostrea gigas, and numerous mortality outbreaks have been observed worldwide. We report the first results of our experimental breeding program using mass selection focused on survival and resistance to OsHV-1 after four generations of selection for two lines. These lines originated from two stocks of adult wild oysters sampled from the Marennes-Oléron Bay in 2008. Each line was spawned in February 2009 to produce the base populations. Both lines were then either protected from OsHV-1 or tested in the field in 2009 where they were exposed to OsHV-1. For each line during 2010 to 2013, one generation per year was produced using either the survivors of the previous generation for the selected group or the oysters protected from OsHV-1 for the control group. After one generation of selection (G1) for both lines, the mean survival of the selected group was 34.5% compared with 12.3% in the control group. For the fourth generation of selection (G4), the survival of the selected group reached 69.0% and the survival of the control group was 7.3%. The gain in survival of the selected C. gigas spat over the control increased by 22.2%, 43.9%, 50.2% and 61.8% for the G1, G2, G3 and G4 generations, respectively. Our study demonstrates that mass selection for survival and OsHV-1 resistance was successful after four generations of selection, thus indicating a significant genetic improvement for the selected trait. A genotype x size interaction was observed with 55.1% of survival in G4 when selected spat were transferred at 1 g versus 89.9% of survival when they were transferred at 3 g. Our study is the first to provide some estimates of the realized heritability for disease resistance using a mass selection scheme in an oyster species with values ranging from 0.34 to 0.63 depending on the size of the oysters exposed to OsHV-1. Oysters selected for their higher resistance to OsHV-1 infection in G4 showed higher growth (58.4 mm – 19.4 ...